(3OjhGf GdYGdes - (3eMehO GdYGde , eMehO GdYGde GdefRdj,J (B1311 (3g` s
(3ChdgG (B:s
(3CeG HYO(B: (3agPg hQjbGJ OhfJ ajgG eG YHK HacQj ef GdbUGFO hGdCTYGQ HCfhGYgG dCgd GdWQjb EfLGH Sgd hChYQ aef QGFM ajgG hefge eHcQ s
(3BNQgG (B:s
(3ef bUjOI aj eOM TjN GdCRgQ GdSjO eUWai GdYQhSj(B: (3dc TCf RgG hLO Ldjd HfTGf GdSdWGf YHOGdYRjR s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B52s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B150 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs